Professional approach importance in auditing of financial statements for tax accounting - Zina Mohammed Sabti Najim Al Askary, Ahmed Kadhim Sendw, Hassan salim mohsin, (Opción, 2019)
The present study is aimed at exploring the importance of a professional approach in auditing financial statements for tax accounting purposes via the inductive method to cover the theoretical aspect of the research. The case study from two different organizations has been selected for data collection, analysis, and interpretation. As a result, the company's failure to provide sufficient evidence to support its expenses was the reason for its rejection by the Financial Authority. In conclusion, limited companies must meet through their financial lists provided to the Financial Authority for the purposes of fiscal accounting.